Exploring Changes in Fishery Emissions and Organic Carbon Impacts Associated With a Recovering Stock - Martin, Angela Helen; Ferrer, Erica M.; Hunt, Corallie A.; Bleeker, Katinka; Villasante, Sebastián (Frontiers in Marine Science, 2022)
International objectives for sustainable development and biodiversity conservation require restoring fish populations to healthy levels and reducing fishing impacts on marine ecosystems. At the same time, governments, retailers, and consumers are increasingly motivated to reduce the carbon footprint of food. These concerns are reflected in measures of the EU Common Fisheries Policy (CFP) and the CFP Reform Regulation, which highlighted a need to move from traditional single-stock management toward an ecosystem approach to fisheries management (EAF). Using publicly available landings and effort data combined with estimates of adult population biomass, we develop methods to explore the potential for lowering emissions intensity and impacts on organic carbon stocks through ending overfishing and rebuilding stocks. We use the recent recovery of European hake (Merluccius merluccius) stocks in the Northeast Atlantic as a case study. With a focus on the hake fisheries of France, Spain, and the United Kingdom, we compare 2008 and 2016 fishing years. We make an initial estimate of the influence of changing stock status on greenhouse gas emissions during the fishery phase from fuel use and investigate the potential disturbance of organic carbon in the ecosystem, specifically via identification of bottom trawling overlap with organic-rich muddy sediments, and directly on storage in hake biomass. Our findings indicate that recovery of the hake stock was associated with reductions in overall emissions intensity from fuel and proportional impact on hake populations, however, total emissions from both fuel and landings increased, as did likely disturbance of sedimentary organic carbon in surface sediments due to benthic trawling. Ultimately, the aims of this analysis are to further explore the climate impacts of fisheries and overfishing, and to inform development of EAF in the EU.